THE DEVELOPMENT OF ANTI MISSOLI SOFTWARE TO REDUCE MISCONCEPTION USING CONCEPTUAL CHANGE TEXT STRATEGY IN SOLUBILITY EQUILIBRIA (Universitas Negeri Surabaya, 2019)
This study aimed to determine the feasibility of Anti Missoli software to reduce misconception using conceptual change text strategy in solubility equilibria. The software feasibility is assessed based of three aspects, i.e (1) content validity and construct validity, (2) practicality based on student response questionnaire and supported by student activity observation, (3) effectiveness based on shifting understanding of student conceptions from misconception to knowing concept. The method of the research used Research and Development (R&D) method with 12 students of class XII science in MAN 1 Gresik which selected based on the preresearch results conducted by researchers. This study was conducted in January 2019. The result showed that Anti Missoli software was used to reduce misconception using conceptual change text strategy in solubility equilibria based of three aspects, i.e (1) The average percentage of content validity is 83.33% - 91.67% with very valid criteria and construct validity is 88.89% - 93.06% in very valid criteria, (2) The average percentage of student positive response is 83.33% - 95.84% in very practical criteria and supported by student activities is 83.33% – 100% in very practical criteria, (3) The average percentage of shifting understanding of student conceptions from misconception to know concept is 86.07% in very effective criteria.Keywords: Software, Misconception, Conceptual Change Text, Solubility Equilibria.